Improvement of dried mangoes through starch finishing - Gamboa, Arthur A.
This study was undertaken to improve the quality and yield of dried mangoes by applying starch as surface coating. Variables studied were type of starch (ordinary or modified) to be used, sweating of the dried mango product before the application of starch, and the manner of applying starch coating (glazed or dusted). Both instrumental and sensory evaluations were made to determine the effects of the variables in the quality characteristics of the finished product. Results revealed that dried mangoes were best coated with maltodextrin with a D.E. level of 9 and should be allowed to sweat before the coating is applied. The product glazed with the starch coating produced the most acceptable dried mango product. It had a "slightly plump" appearance, "yellow" color, "slight mango flavor", "chewy" texture and a general acceptability of "liked moderately".